The importance of vertical linkages for the innovation activity of medium-high and high technology industries in Poland - Piotr Dzikowski (International Journal of Management and Economics, 2016)
This study investigates how vertical linkages impact the innovative activity of both medium-high and high technology industries in Poland. The data for this research were collected in structured telephone or e-mail interviews with managers and company owners. The final data set includes 1,355 firms. The analysis is based on probit modeling that allows us to determine the probability of innovative activity in relation to a number of supplier and customer groups or a type of vertical linkage. We find that the number of suppliers and customers shape innovative activity; specifically, the more groups of suppliers and customers the higher level of innovative activity. This analysis suggests that appropriate suppliers and customers can greatly accelerate innovation activity.
Keywords: O32; O33; 650; innovative activity; vertical linkages; industry; HT; MHT